Efficient conversion of cellulose to levulinic acid by hydrothermal treatment using zirconium dioxide as a recyclable solid acid catalyst - Joshi, Sunil S.; Zodge, Amit D.; Pandare, Kiran V.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2014)
Conversion of cellulose into platform chemicals is essential for sustainable development of the chemical industry. With this aim, single step hydrothermal conversion of cellulose to industrially important levulinic acid using zirconium dioxide as a catalyst has been investigated. A remarkably high yield (53.9 mol %) of levulinic acid with excellent accountability and total conversion of cellulose has been achieved at 180 degrees C reaction temperature and reaction time of 3 h with 2 wt % of catalyst and 2 g of cellulose. The major products identified were levulinic acid (LA), formic acid (FA), 5-hydroxymethylfurfural (5-HMF), furfural, and humins. Formation of humins during cellulose hydrolysis and dehydration was observed and is also confirmed by NMR and FTIR analysis. The effect of various reaction parameters such as temperature, time, substrate concentration, and catalyst loading on conversion and selectivity has been studied. The catalyst has been regenerated and recycled several times without any loss of activity and selectivity.